Формування художніх орієнтацій студентів засобами музики та хореографії в умовах цифрового освітнього середовища - Чурікова-Кушнір Ольга; Churikova-Kushnir Olga (Видавництво «Код», 2025)
Резюме. У статті досліджується процес формування художніх орієнтацій студентів у галузі музики та хореографії в умовах цифрового освітнього середовища. Розкриваються основні компоненти художніх орієнтацій (когнітивно-поведінковий, емоційно-ціннісний, мотиваційно-смисловий та творчо-рефлексивний) та їхній взаємозв’язок і значення у професійній підготовці майбутніх педагогів музики і хореографії в умовах цифрового освітнього середовища.

Abstract. The article examines the process of forming students’ artistic orientations in the field of music and choreography within a digital educational environment. It reveals the main components of artistic orientations (cognitive-behavioral, emotional-value, motivational-semantic, and creativereflective) and their interrelationship and significance in the professional training of future music and choreography teachers in digital educational settings. It is determined that the cognitive-behavioral component ensures the acquisition of theoretical knowledge and development of practical skills, integrating modern information and communication technologies for modeling, analyzing, and implementing artistic ideas in creative activities; the emotional-value component promotes deep emotional immersion in the arts, forms stable value orientations, develops aesthetic sensitivity and motivation for creativity, while digital resources enhance possibilities for interactive emotional experience; the motivational-semantic component stimulates intrinsic interest in creative activity, supports the pursuit of self-expression and innovation, promotes the mastery of modern digital tools as means of realizing artistic ideas; the creative-reflective component forms the ability for self-critical analysis, self-assessment of creative activity results and their integration into further professional development, activating the use of digital platforms for feedback and video analysis. Special attention is given to the role of information and communication technologies, which contribute to deepening theoretical knowledge, developing analytical and practical skills, forming motivation, creative self-realization, and the ability for self-reflection. The use of modern digital tools is noted, such as multimedia platforms, audio and video editors, performance video analysis, and online feedback tools, which ensure individualization of the educational process and increase its effectiveness. It is determined that digital technologies not only expand the traditional possibilities of arts education but also become a key factor in forming a comprehensively competent, creative, and competitive specialist in the field of music and choreography. Further research should be directed toward developing new methodologies for integrating digital tools into arts pedagogy, which will ensure the effectiveness and depth of professional training for future educators.
Formation of artistic orientations of students through music and choreography in the conditions of digital educational environment
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: художні орієнтації; музика; хореографія; цифрове освітнє середовище; цифрові інструменти; професійна підготовка; інформаційно-комунікаційні технології